Microbiological activity of a soil under different uses and its relation with physico-chemical variables - Di Ciocco, Cesar Augusto; Sandler, Rosana Veronica; Falco, Liliana Beatriz; Coviella, Carlos Eduardo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Much of the microbial processes that contribute to agroecosystems fertility and nutrient cycling take place in the soil. This nutrient cycling depends critically on the soils’ microbiological activity, which is, in turn, mediated by the structure and functioning of the edaphic biota. In this context, the objective of this work was to determine if the microbial activity can be a good indicator of soil use intensity, by analyzing: 1- if differences in soil use intensity are related to differences in microbiological activity estimated through soil respiration and enzymatic activity, and 2- the possible relationships between these variables and physico-chemical variables. Samplings were conducted every three months between 2008 and 2010 in fields in the Buenos Aires province on argiudoll soils under different land uses: 1- Intensive continuous agriculture, 2- Recent agriculture and 3- Naturalized grasslands. Three sampling sites (replicates) were selected for soil use and five samples were collected per replicate and date. Microbial activity was then assessed by measuring soil respiration and nitrogenase enzyme activity, and physico-chemical variables were measured as well. Data were analyzed by means of a Kruskal-Wallis test (P < 0.05). A non- parametric analysis was performed (Spearman multiple correlation) between the physicochemical and microbiological variables. The different uses of the same soil showed significant differences in microbiological activity. Soil respiration was higher in the naturalized grasslands and lower in the continuous agricultural system. Nitrogenase activity was higher in the naturalized grasslands, intermediate in the recent agricultural system and lower in the continuous agriculture fields. The physico-chemical variables measured were less consistent in detecting differences among soil uses. Significant correlations were detected between microbiological activity and some of the physico-chemical variables measured. The results show that microbiological activity can be useful to detect differences in soil use intensity.